China reinterpreted : staging the Other in Muromachi Noh theater - Yip, Leo Shingchi (Lexington Books, 2016)
This book is a comprehensive study of Chinese figures and motifs in medieval Japanese noh theater. It explores the images of China and their implications constructed in the so-called "karagoto-mono" (Chinese plays) that reflect the artistic preferences, as well as the cultural and sociopolitical sentiments towards China held by Muromachi noh artists and audiences